OPINI AUDIT GOING CONCERN DAN FAKTOR YANG MEMPENGARUHINYA - Indira Shinta Dewi (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
Obtaining empirical evidence of how the effect debt default,finacial distress , Audit Opinion Preceding Years is the goal of this study This study focused on manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2019-2021. 317 number of observations sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is logistic regression analysis. The analysis showed that the profitability, and leverage has no effect on tax avoidance. Sales growth has negative effect on tax avoidance